2020
DOI: 10.3390/ijms21186555
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive Effect of Dietary Anthocyanins against Gastrointestinal Cancers: A Review of Recent Advances and Perspectives

Abstract: Anthocyanins are a group of dietary polyphenols, abundant mainly in fruits and their products. Dietary interventions of anthocyanins are being studied extensively related to the prevention of gastrointestinal (GI) cancer, among many other chronic disorders. This review summarizes the hereditary and non-hereditary characteristics of GI cancers, chemistry, and bioavailability of anthocyanins, and the most recent findings of anthocyanin in GI cancer prevention through modulating cellular signaling pathways. GI ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 249 publications
(264 reference statements)
0
19
0
1
Order By: Relevance
“…Indeed, a recent study indicates the intake of 300 g of red raspberries results in the identification of 18 different anthocyanin-derived metabolites [ 77 ]. Basically, delphinidin-based anthocyanins are transformed into 2,4,6-trihydroxybenzaldehyde, gallic, and syringic acids, while syringic, 4-hydroxybenzoic, and vanillic acids are the primary metabolites of malvidin, pelargonidin, and peonidin glucosides, respectively [ 111 , 117 ]. Cyanidin glycosides can produce around 35 metabolites, 31 being found in urine samples, 28 in faeces, and 17 in the circulatory system, where the main ones are 2,4,6-trihydroxybenzaldehyde, ρ -coumaric, protocatechuic and vanillic acids, and phenolic conjugates (e.g., hippuric, phenylacetic, and phenylpropenoic acids) [ 77 , 118 ].…”
Section: Anthocyanins’ Bioavailability and Metabolismmentioning
confidence: 99%
“…Indeed, a recent study indicates the intake of 300 g of red raspberries results in the identification of 18 different anthocyanin-derived metabolites [ 77 ]. Basically, delphinidin-based anthocyanins are transformed into 2,4,6-trihydroxybenzaldehyde, gallic, and syringic acids, while syringic, 4-hydroxybenzoic, and vanillic acids are the primary metabolites of malvidin, pelargonidin, and peonidin glucosides, respectively [ 111 , 117 ]. Cyanidin glycosides can produce around 35 metabolites, 31 being found in urine samples, 28 in faeces, and 17 in the circulatory system, where the main ones are 2,4,6-trihydroxybenzaldehyde, ρ -coumaric, protocatechuic and vanillic acids, and phenolic conjugates (e.g., hippuric, phenylacetic, and phenylpropenoic acids) [ 77 , 118 ].…”
Section: Anthocyanins’ Bioavailability and Metabolismmentioning
confidence: 99%
“…Due to their structure, they are effective antioxidant molecules able to decrease the production of free radicals through Fenton reaction [ 67 , 68 , 69 ]. Moreover, polyphenols can directly interact with various enzymes, resulting in anti-inflammatory, anti-microbial, anti-viral, anti-aging, anticancer properties and they also show neuroprotective effects [ 70 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Introductionmentioning
confidence: 99%
“…The phenolic structure of anthocyanins is responsible for their antioxidant and anti-inflammation activity, mainly due to their ability to scavenge ROS [16]. In addition, it was demonstrated that anthocyanins can inhibit CRC, interfering in the cell cycle and inducing antiproliferative effects and apoptosis [17][18][19]. Data from nonrandomized controlled trials demonstrate that anthocyanins may play an active role in the prevention of CRC in humans [19].…”
Section: Introductionmentioning
confidence: 99%